2017
DOI: 10.1002/anie.201702955
|View full text |Cite
|
Sign up to set email alerts
|

Switching Between Giant Positive and Negative Thermal Expansions of a YFe(CN)6‐based Prussian Blue Analogue Induced by Guest Species

Abstract: The control of thermal expansion of solid compounds is intriguing but remains challenging. The effect of guests on the thermal expansion of open-framework structures was investigated. Notably, the presence of guest ions (K ) and molecules (H O) can substantially switch thermal expansion of YFe(CN) from negative (α =-33.67×10 K ) to positive (α =+42.72×10 K )-a range that covers the thermal expansion of most inorganic compounds. The mechanism of such substantial thermal expansion switching is revealed by joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 62 publications
5
83
4
Order By: Relevance
“…178 In this way, a ZT of 1.6 was reported for a synthetic alloy of com- 182 The cavities are larger than those of the simple oxides and fluorides, so there is often solvent, typically water, by Goodwin et al, 100 which showed that by including an intercalant species the transverse vibrations are dampened and NTE is suppressed (Figure 6b). As a point of interest, this dampening of NTE via intercalation is also observed for a related (non-ReO 3 -type) porous rare earth cyanide compound, 184 and illustrates the similar structure-property relationship between the systems. (Figure 7) (a), a potential hydrogen storage material, which is attractive because it degrades to H 2 gas and solid YB 4 under 1-5 bar of partial hydrogen pressure (i.e.…”
Section: Inorganicssupporting
confidence: 52%
“…178 In this way, a ZT of 1.6 was reported for a synthetic alloy of com- 182 The cavities are larger than those of the simple oxides and fluorides, so there is often solvent, typically water, by Goodwin et al, 100 which showed that by including an intercalant species the transverse vibrations are dampened and NTE is suppressed (Figure 6b). As a point of interest, this dampening of NTE via intercalation is also observed for a related (non-ReO 3 -type) porous rare earth cyanide compound, 184 and illustrates the similar structure-property relationship between the systems. (Figure 7) (a), a potential hydrogen storage material, which is attractive because it degrades to H 2 gas and solid YB 4 under 1-5 bar of partial hydrogen pressure (i.e.…”
Section: Inorganicssupporting
confidence: 52%
“…The inserted species within cavities in the structure are adjacent to the linkers and so reduce the amplitudes of their transverse vibrations. Redox insertion of only 6% Li into Fe-doped ScF 3 switches the TEC from negative to positive (Chen et al, 2017 ), and the same change is found when K + or H 2 O is inserted into the channels of the cyanide framework material YFe(CN) 6 (Gao et al, 2017 ).…”
Section: Intrinsic Nte Mechanismsmentioning
confidence: 92%
“…26 The switching between PTE and NTE in the Prussian blue analogue YFe(CN) 6 was recently reported by Chen and co-authors. 27 However, there are no reports on the switching between PTE and NTE for highly porous MOFs. Herein, we present the rst report for simultaneous positive and negative thermal expansion for the same MOF structure, under different conditions applied.…”
Section: Introductionmentioning
confidence: 99%